Eosinophilic lingual tonsillitis induced by sublingual immunotherapy: A case series. Issue 11 (6th August 2020) - Cavaliere, Carlo; Luperto, Paolo; Gnesutta, Michele; Incorvaia, Cristoforo; Rosati, Davide; Masieri, Simonetta
Abstract: The new observation of eosinophilic lingual tonsillitis as a possible adverse reaction to sublingual immunotherapy is likely to stimulate new investigations aimed at improving the understanding of the mechanisms of biodistribution of extracts placed at the sublingual level. Abstract : The new observation of eosinophilic lingual tonsillitis as a possible adverse reaction to sublingual immunotherapy is likely to stimulate new investigations aimed at improving the understanding of the mechanisms of biodistribution of extracts placed at the sublingual level.